Reconstruction of Legal Subjects in Ushul Al-fiqh: Development and Interconnectivity Analysis in the Contemporary Era - Setyawan, Rahmad; Sodik, Nur; Khairuddin, Khairuddin; Adnani, Fahlul Ulum Ahmad (Faculty of Shariah UIN Ponorogo, 2025)
In general, legal subjects refer to entities that have rights and obligations in the legal system. This study aims to reconstruct legal subjects in ushul al-fiqh and their development in the contemporary era. Methodologically, this study is a library research with an interconnective approach. Data was collected from various literature sources, such as laws, court decisions, books, works of scholars, the Qur'an, hadith, encyclopedias, dictionaries, journals, magazines, and other relevant sources. The results of the study show that, in line with the times, the scope of legal subjects in ushul al-fiqh has undergone development. Previously, legal subjects only included individuals who met the requirements of being ‘aqil and baligh, but now they also include legal entities. The reconstruction of legal subjects in ushul al-fiqh and its development in the contemporary era shows the interconnection between ushul al-fiqh and modern sciences, such as legal sociology, legal anthropology, legal philosophy, and modern legal science. This is reflected in a number of laws and regulations in Indonesia that recognize legal entities as legal subjects. Through an interconnective approach, it can be understood that ushul al-fiqh as the epistemological foundation of Islamic law is capable of dialoguing with various modern fields of science in responding to social changes without losing its theological roots.